Wavelet transform algorithm of daily load graphs for choosing parameters of hybrid energy storage - O. V. Arkhipova; N. N. Dolgikh; S. Yu. Dolinger; V. Z. Kovalev; D. S. Osipov (Омский научный вестник)
The paper presents an algorithm for frequency decomposition of daily load graphs based on a discrete wavelet transform. This algorithm makes it possible to choose the optimal type of wavelet function, optimal level and wavelet decomposition tree. The inverse wavelet transform (recovery) along a single branch of the approximating coefficient allows obtaining the lowfrequency component of the power graph for selecting the optimal mode of the hybrid energy storage battery. The detailing branch of the wavelet coefficients determines the operating mode of the supercapacitor. A numerical experiment is built on the basis of data obtained using certified equipment.